Effect of Virtual Retraining Courses on the Knowledge, Attitude and Performance of Konarak Health Workers in the Malaria Elimination Program in 2022 - Mojtaba Salimi Bani; Mehdi Ghassabi Chorsi; Roghayeh Ershad Sarabi (پیاورد سلامت)
Background and Aim: Malaria is one of the health challenges in many countries worldwide. Iran is among the countries that have prioritized a malaria elimination program, aiming to interrupt local transmission of the disease by 2025. Health workeres (community health workers) play an important role in primary healthcare for identifying, controlling, and preventing malaria. Keeping their knowledge and skills up-to-date through continuous training can be effective in the success of this program. Virtual training is a modern educational method that facilitates such training courses. This study aimed to investigate the impact of virtual retraining courses on the knowledge, attitude, and performance of konarak health workers in implementing the malaria elimination program in 2022. Materials and Methods: This research was a quasi-experimental study with a single-group pre-test and post-test design. The population included 69 individuals who were enrolled using a census method. Initially, a pre-test was conducted to assess the baseline level of knowledge, attitude, and performance of participants regarding malaria elimination strategies. Then, the educational intervention was delivered virtually, followed by a post-test to evaluate the outcomes. The educational content was provided in eight 45-minute sessions by an instructor from the Health worker Training Center using the Sky Room platform. Data collection was performed using a researcher-made questionnaire. Content validity of the questionnaire was confirmed, and its reliability was assessed in a pilot study prior to the training by the responsible expert; the Cronbach’s alpha coefficient of the questionnaire items was calculated at an acceptable level (r=0.83). Data were analyzed using SPSS software and paired t-tests. Results: Out of 69 participants, 40 (58%) were male and 29 (42%) female. Comparison of pre-test and post-test results showed that the mean scores of knowledge, attitude, and performance of health workeres increased by 1.05, 1.2, and 1.17 units respectively after the training, and these differences were statistically significant (P=0.000). Conclusion: Based on the results, considering the advantages of virtual training such as easy access, lower cost, and wide coverage, this method is recommended as a strategy for educational programs for healthcare staff.